Executive functioning in patients with blepharospasm in comparison with patients with hemifacial spasm Funções executivas em pacientes com blefaroespasmo em comparação a pacientes com espasmo hemifacial - Fernando Machado Vilhena Dias; Flávia C.P. Doyle; Arthur Kummer; Francisco Cardoso; Paulo Caramelli; Antônio Lúcio Teixeira (Arquivos de Neuro-Psiquiatria)
BACKGROUND: Non-motor symptoms have been described in primary dystonia, but the results on cognitive impairment in this condition are discordant. Blepharospasm (BM) is a type of primary focal dystonia characterized by recurrent and involuntary eye blinking. Hemifacial spasm (HS), a condition with different pathophysiology, constitutes an adequate control group when investigating non-motor disturbances in BM. OBJECTIVE:To compare the performance of patients with BM and HS in the Frontal Assessment Battery (FAB). METHOD: Twenty-two patients with BM and 29 patients with HS were submitted to the FAB and the Mini-Mental State Examination (MMSE). FAB scores were compared between the two groups. Correlations between FAB and sociodemographic and clinical variables were calculated. RESULTS: BM group was not different from HS in relation to gender, age, length of symptoms, educational level and performance in the MMSE. FAB scores were also similar in both groups. FAB scores correlated negatively with age and positively with educational level and MMSE scores. CONCLUSION: Executive functioning as assessed by FAB is not altered in BM in comparison with HS. INTRODUÇÃO: Alterações não-motoras são descritas na distonia primária, embora sejam conflitantes os resultados sobre prejuízo cognitivo nessa condição. Blefaroespasmo (BE) é um tipo de distonia primária focal caracterizada por contrações recorrentes e involuntárias das pálpebras. Espasmo hemifacial (EH), cuja fisiopatologia é distinta do BE, constitui bom grupo controle quando se investiga alterações não-motoras no BE. OBJETIVO: Comparar o desempenho de pacientes com BE e com EH na Bateria de Avaliação Frontal (BAF). MÉTODO: BAF e Mini-Exame do Estado Mental (MEEM) foram administrados a 22 pacientes com BE e 29 com EH. Os escores da BAF foram comparados entre os dois grupos. Correlações entre resultados na BAF e variáveis sócio-demográficas e clínicas foram calculadas. RESULTADOS: Os grupos BE e EH foram semelhantes quanto a gênero, idade, duração dos sintomas, escolaridade e desempenho no MEEM. Os escores dos dois grupos na BAF foram também similares, correlacionando-se negativamente com idade e positivamente com escolaridade e desempenho no MEEM. CONCLUSÃO: As funções executivas avaliadas pela BAF não estão alteradas no BE em relação ao EH.